Revitalizing Nationalism through Authentic Urban Spaces: The Role of Advanced Social Intelligence and Sustainability - Suparno Suparno; Eko Nursanty; Supot Rattanapun (PT. Multidisciplinary Press Indonesia, 2024)
In an increasingly globalized world, the preservation of national identity through authentic urban spaces faces significant challenges. As cities expand and modernize, the balance between sustainability, cultural heritage, and technological advancements becomes more difficult to achieve. This paper explores the intersection of sustainability and advanced social intelligence in urban planning, focusing on how these multidisciplinary approaches can help revitalize nationalism by maintaining the authenticity of space and place. Sustainability initiatives in urban development often prioritize environmental efficiency and smart growth but may inadvertently threaten the cultural and historical elements that define a nation's identity. By leveraging advanced social intelligence, such as data-driven decision-making, community participation, and real-time analytics, cities can manage growth while protecting the cultural integrity of their urban landscapes. This paper highlights successful case studies from both global and local contexts where urban spaces have been carefully preserved and modernized in ways that reinforce national pride and identity. Through a comprehensive analysis, this study argues that preserving the authenticity of urban spaces—especially historical districts, architectural landmarks, and culturally significant areas—plays a critical role in sustaining national identity in the face of rapid urbanization. Furthermore, it emphasizes the need for a multidisciplinary approach, integrating architecture, urban planning, technology, and sociology to create a sustainable urban framework that respects cultural heritage while fostering innovation. The paper offers insights into how advanced social intelligence and sustainability can be effectively combined to support the authenticity of urban spaces, thereby contributing to a renewed sense of nationalism and cultural cohesion in modern cities.